Darifenacin reveals a functional role for M4 muscarinic acetylcholine receptors in guinea pig gallbladder - (:unkn) unknown (My University, 2002)
Objective: Previous studies have revealed the presence of M1 to M4 muscarinic receptors in guinea pig gallbladder, with M 3 and M4 receptors being claimed to mediate contractions. Methods: In the present study, cumulative concentration-response curves to carbachol were constructed in the absence and presence of darifenacin, which has greater selectivity for M3 over M4 receptors, in guinea-pig gallbladder. Results: Darifenacin caused concentration-dependent dextral shifts of the carbachol curve, however, at 1 μM, it also caused a degree of insurmountable antagonism. Using a novel analytical approach, we obtained a pKB estimate for darifenacin (7.51 ± 0.14) that is in excellent agreement with its affinity for M2/M4, but not M3 receptors. Conclusion: Given our previous demonstration that M2 receptors are unlikely to contribute to muscarinic contractions in this tissue, our current findings provide pharmacological evidence for a predominant role of M4 muscarinic receptors in guinea pig gallbladder contractions.
Keywords: Contraction; Darifenacin; Gallbladder; Guinea-pig; Muscarinic receptor